Juridical Analysis of Baby Dumping and Perpetrator Criminal Liability under the Penal Code and Child Protection Law - Farhan Naufal Ferdiansyah; Rangga Jayanuarto; Hendi Sastra Putra; Mikhorardinata Mikhorardinata (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The phenomenon of baby dumping in Indonesia is a complex criminal offense intersecting with moral, social, and legal dimensions. This study aims to analyze the regulatory framework for baby abandonment regarding the enactment of Law No. 1/2023 (the New Criminal Code/KUHP) and Law No. 35/2014 on Child Protection. Using a normative legal research method with a statutory approach, this study examines primary and secondary legal sources. The findings indicate that Articles 429–431 of the New Criminal Code reorient the provisions on child abandonment from the old Criminal Code toward a progressive justice system emphasizing restorative justice. However, these provisions still overlap with the Child Protection Law, which acts as a lex specialis by imposing more severe criminal sanctions. The novelty of this research lies in its critical analysis of legal synchronization precisely at the transition moment of the National Criminal Code's enactment as of January 2026, mapping the jurisdictional dualism between codified general criminal law and child protection law. Consequently, the success of law enforcement at this juncture heavily depends on the readiness of law enforcement officials, regulatory harmonization, and the strengthening of community-based preventive strategies through inter-institutional synergy and increased public awareness.